2009
DOI: 10.1111/j.1423-0410.2009.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of apheresis‐derived platelets treated with ultraviolet light combined with either amotosalen‐HCl (S‐59) or riboflavin (vitamin B2) for pathogen‐reduction

Abstract: Pathogen reduction technology-treated PLTs remained comparable to untreated units throughout 7 days of storage. Mitochondria-based oxidative respiration appeared up-regulated after the riboflavin-based PRT. Compared to the psoralen-based PRT, this resulted in significantly better ATP maintenance and in vitro function during the last storage period (d7, d8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
90
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 35 publications
14
90
4
Order By: Relevance
“…TRAP-6 stimulation induced an increase in P-selectin and PS on platelets adhering to fibrinogen until day 7 but did not have any additional effect on the expression of P-selectin or PS on platelets adhering to collagen beads. The reduced response to TRAP-6 at the end of storage (lower fibrinogen binding and lower expression of P-selectin on adherent platelets) is in accordance to other studies using aggregometry to assess platelet function [25][26][27].…”
Section: Discussionsupporting
confidence: 73%
“…TRAP-6 stimulation induced an increase in P-selectin and PS on platelets adhering to fibrinogen until day 7 but did not have any additional effect on the expression of P-selectin or PS on platelets adhering to collagen beads. The reduced response to TRAP-6 at the end of storage (lower fibrinogen binding and lower expression of P-selectin on adherent platelets) is in accordance to other studies using aggregometry to assess platelet function [25][26][27].…”
Section: Discussionsupporting
confidence: 73%
“…The most likely explanation for the discrepancies between our results and the study by Stivala et al 1 and others [4][5][6] is the fact that we isolated platelets from the storage milieu in order to explore their intrinsic functional properties, independently of the storage milieu which may have an inhibitory-yet-reversible effect on platelet responsiveness. We also looked at the reactivity of platelets in their storage milieu and, indeed, found there was already inhibition of platelet aggregation in response to ADP on Day 1.5, and to collagen on Day 6.5, which was, however, similar between the untreated and the IBS-PCs 2 (see Online Supplementary Figure S2B).…”
contrasting
confidence: 55%
“…5,6 In addition, in our study, the pH values of the storage milieu remained similar in both untreated and IBS-PCs, while Stavila et al reported a significant decrease in pH in IBS-treated PCs compared to untreated units by Day 1.5. Thus, independently of the washing procedure, differences in the overall initial collection procedure and/or storage conditions may play a role and could explain such differences between centers.…”
mentioning
confidence: 58%
“…Further, there is an unbalance between APCs gamma-irradiated at the day of transfusion and those irradiated in advance in favor of the former. It would be of interest to evaluate in more detail both the association between transfusion efficacy and the time frame between gamma irradiation of APCs and transfusion as well as the effect of treatment by riboflavin or amotosalen-HCI plus ultraviolet light also including the time frame between irradiation and transfusion, which in the later procedure could be up to 7 days [26]. …”
Section: Discussionmentioning
confidence: 99%